Theoretical, Conceptual, and Operational Aspects in Simulation Training With Rapid Cycle Deliberate Practice: An Integrative Review - de Oliveira, Hudson Carmo; Campos, Juliana Faria; de Souza, Lucimar Casimiro; de Bakker, Gabriela Barcellos; Ferreira, Luciana Lopes Busquet; da Silva, Rodrigo Nogueira; Dos Santos Pires, Paula Rodrigues; Brandão, Marcos Antônio Gomes (Simulation in healthcare : journal of the Society for Medical Simulation, 2024)
An integrative review following Whittemore and Knafl's 5-stage approach (problem identification, literature search, data evaluation, data analysis, and presentation) was conducted to synthesize the evidence on the theoretical, conceptual, and operational aspects of simulation training with rapid cycle deliberate practice (RCDP). After the literature search, 2 reviewers independently read and critically evaluated primary studies using the eligibility criteria. A third more experienced reviewer solved disagreements between the reviewers.This review included 31 articles. Eight themes were identified and grouped into 2 pre-established categories: theoretical/conceptual and operational aspects. The first category had the following 3 themes: definition of RCDP, concepts related to the principles of RCDP, and theories underpinning RCDP. The second category had the following 5 themes: total training time, number of participants in the training, training system, first scenario without intervention, and progressive difficulty. This review showed that knowledge about RCDP is still under construction. As a new simulation strategy, there are some theoretical, conceptual, and operational differences in the studies applying RCDP interventions as simulation training.